Trajectories of Mediterranean Diet Adherence in risk of hypertension in China: Results from the CHNS study, 1997-2011 - Gao, M; Wang, F; Shen, Y; Zhu, X; Zhang, X; Sun, X (MDPI, 2018)
Evidence indicates that longitudinal changes in dietary patterns may predict variations in blood pressure (BP) and risk of incident hypertension. We aimed to identify distinct trajectories in the levels of Mediterranean diet adherence (MDA) in China and explore their association with BP levels and hypertension risk using the China Health and Nutrition Survey 1997–2011 data. Three levels of MDA were constructed. The trajectories in these levels were constructed using group-based trajectory modeling. A Cox proportional hazards model was used to measure the association between MDA trajectory groups and the risk of incident hypertension after adjusting for covariates. Finally, 6586 individuals were included. Six distinct MDA trajectory groups were identified: persistently low and gradual decline; rapidly increasing and stabilized; persistently moderate; slightly increasing, steady, and acutely descending; slightly decreasing and acutely elevated; and persistently high. The systolic BP and diastolic BP were significantly lower in trajectory groups with rapidly increasing and stabilized MDA; slightly increasing, steady, and acutely descending MDA; and persistently high MDA. Cox regression analysis showed that the risks of developing hypertension were relatively lower in the group with slightly increasing, steady, and acutely descending MDA (hazard ratio (HR) = 0.17, 95% confidence interval (CI): 0.09–0.32) and the group with rapidly increasing and stabilized MDA (HR = 0.32, 95% CI: 0.23–0.42), but the risk was the highest in the trajectory with persistently moderate MDA (HR = 0.96, 95% CI: 0.84–1.08). In conclusion, MDA in China was categorized into six distinct trajectory groups. BP was relatively lower in trajectory groups with initially high or increasing MDA levels. Greater MDA was significantly associated with a lower risk of developing hypertension.